Designing Esp Learning Instruction In Managements Study Program: A Survey On Students' Needs - Danial, Haris; Agriyanti Mestari , Sri; Fatmawaty Mohammad, Titien (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this research is basically oriented towards the output of teaching materials based on English for Specific Purposes (ESP) in the Management Study Program, Faculty of Economics and Business, State University of Gorontalo. The research objectives are: (1) identifying the English curriculum at FEB, namely in the management study program, student character and needs, concept analysis, formulation of learning objectives, and analyzing teaching materials; (2) designing ESP-based English materials; (3) designing the format of ESP-based English teaching materials. The research was conducted at the State University of Gorontalo, Faculty of Economics and Business, especially in the Management study program. The research method uses a research and development design (Research & Development) which includes 9 (nine stages) including: 1) developing information and research, 2) planning, 3) developing an initial product form, 4) initial field testing, 5) product revision, 6) core field test, 7) operational product revision, 8) operational field test, and 9) final product revision. This form of development was modified with a constructivist approach. The result showed tat students have a lack of experience studying English. Moreover, most students say that their English proficiency level is average. Most students say they are unable to fluently speak. The last category pertains to the students' desire to use proper grammar. The last phase of the need assessment is the target needs. The five areas of learning needs include input, procedure, setting, student role, and the teacher's role. The students want to participate in group dialogue and role play as part of the curriculum, in addition to talking and role playing. The students desire to have group dialogue and role play prior to undertaking the assignment.